Evaluating the pharmacokinetics and safety of blonanserin tablets and Lonasen®: a randomized, open-label, two-period, two-sequence, self-crossover phase I clinical trial - Qiu, Bo; Song, Haojing; Sun, Xue; Ding, Congyang; Du, Runxuan; Bai, Wanjun; Dong, Zhanjun (Frontiers in Pharmacology, 2025)
ObjectiveThis study evaluated the pharmacokinetic and safety profiles of generic and original blonanserin tablets under fasting and postprandial conditions, and the bioequivalence of two formulations to obtain sufficient evidence for abbreviated new drug application.MethodsA randomized, open-label, two-period, two-sequence, self-crossover bioequivalence study was conducted to assess the bioequivalence of the test and reference blonanserin tablets under fasting and postprandial conditions. Eligible healthy individuals received a single 4-mg dose of either the test or reference blonanserin tablet, followed by a wash out period of 14 days. Serial blood samples were collected for up to 72 h after administration during each period, and the plasma concentrations of blonanserin were determined using a validated method. The non-compartmental method was used to calculate the primary pharmacokinetic parameters, and the geometric mean ratios for the PK parameters of the test drug to those of the reference drug, along with the corresponding 90% confidence intervals, were obtained for bioequivalence analysis. Throughout the study, a safety evaluation was conducted.ResultsUnder both fasting and postprandial conditions, the pharmacokinetic parameters of the test drug were found to be similar to those of the reference drug. The 90% confidence intervals (CIs) of the geometric mean ratios of the test to reference formulations were 97.79%–118.28% for peak concentration (Cmax), 92.35%–111.78% for the area under the curve from zero to the last measurable concentration (AUC0-t) and 92.88%–111.91% for the AUC from zero to observed infinity (AUC0-∞) under fasting conditions, 88.65%–103.20% for Cmax, 95.89%–106.81% for AUC0-t and 96.02%–106.91% for AUC0-∞ under postprandial conditions, all of which were within the accepted bioequivalence range of 80.00%–125.00%. Both the test and reference formulations were well-tolerated, and no serious adverse events related to the study drug were reported during the study.ConclusionThe bioequivalence of blonanserin tablets, both test and reference, was confirmed in healthy Chinese subjects under fasting and postprandial conditions, meeting the predetermined regulatory criteria for both formulations. Both formulations were found to be safe and well tolerated.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/index.html, identifier CTR20230703.